2005
DOI: 10.1177/089686080502500211
|View full text |Cite
|
Sign up to set email alerts
|

Oral Protein-Energy Supplements in Peritoneal Dialysis: A Multicenter Study

Abstract: Background Protein-energy malnutrition is prevalent in peritoneal dialysis (PD) patients and is associated with increased morbidity and mortality. Objective To evaluate the impact of prophylactic treatment with an oral protein-energy supplement (Protenplus; Fresenius AG, Bad Homburg, Germany) on nutritional parameters in patients starting PD. Design Prospective, multicenter, randomized study of group A patients (Protenplus, n = 35) and group B (controls, n = 30), with evaluations at baseline and at 6 and 12 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 33 publications
1
23
0
3
Order By: Relevance
“…12 In another study, daily protein supplements were added to the meal of incident-PD patients, who were then followed-up for 12 months. 20 The mean albumin level of 90 patients was 3.75 g/dL, and no significant increase was observed in these studies following their completion. 12 However, patients with peritonitis were not excluded from these studies.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…12 In another study, daily protein supplements were added to the meal of incident-PD patients, who were then followed-up for 12 months. 20 The mean albumin level of 90 patients was 3.75 g/dL, and no significant increase was observed in these studies following their completion. 12 However, patients with peritonitis were not excluded from these studies.…”
Section: Discussionmentioning
confidence: 65%
“…12 However, patients with peritonitis were not excluded from these studies. During their follow-up periods, 12,20 Eustace et al revealed that oral essential AAs are more effective in patients with very low serum albumin levels than in patients who have subnormal albumin levels. 21 In our study, the albumin levels were around 2.8 g/dL, which is lower than albumin levels in patients who were enrolled in the other studies referenced herein, and data from patients with peritonitis were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…B. eine PEG-Sonde. Laut Marsen [18] [20]. Die PEG-Anlage, welche eine Nahrungszufuhr unabhängig vom Appetit sicherstellen könnte, ist bei erwachsenen Peritonealdialysepatienten kontraindiziert.…”
Section: Resultsunclassified
“…Dietary advice encouraging patients on PD to eat more protein has been shown to be difficult to implement (Sutton et al 2007, Braglia Tarpey 2012, and use of oral nutritional supplements is common. Despite evidence that supplementation is effective in the patients undergoing HD (Kalantar-Zadeh et al 2011, Malgorzewicz et al 2011, studies report both improvement (Moretti et al 2009) and poor effectiveness of oral nutritional supplementation in the PD group (Teixido-Planas et al 2005, Poole & Hamad 2008. Most of these authors called for randomised controlled trials to further investigate the efficacy or otherwise of oral supplementation in the PD population.…”
Section: Literature Reviewmentioning
confidence: 99%